A New Image Encryption Method Using an Optimized Smart Codebook - Rami Sihwail; Dyala Ibrahim (Human Behavior and Emerging Technologies)
Information attacks have increased worldwide as more information is available in digital form. Image encryption is essential to prevent attackers from unauthorized access to confidential images. In this paper, we introduce a novel image encryption method called the smart codebook, which combines an intelligent codebook technique with the RSA (Rivest–Shamir–Adleman) algorithm. The proposed method is designed to be dynamic as it selects the most effective codebooks in encrypting each image to increase its ambiguity. The smart codebook method divides an image into several segments based on image dimensions, and multiple random codebooks are generated for each segment. Moreover, images go through several processing stages before they are converted into cipher images, including noise, segmentation, and encryption. The best codebooks are selected to create the encrypted image in the next stage. Finally, the RSA algorithm sends the recipient the code books with the cipher image. The evaluation of the proposed smart codebook depends on several factors, including entropy, unified averaged changed intensity (UACI), number of changing pixel rate (NPCR), and correlation coefficient analysis. The assessment of the proposed encryption method demonstrates its resilience against cryptographic attacks, affirming its security and precision. The results show an impressive improvement in securing images compared to previous related efforts.